2016
DOI: 10.1016/j.catena.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic geomorphic change as a potential generator of renewable geologic resources in the humid Pampa of Argentina

Abstract: The nature and amount of sediments in various lakes, intermittent swampy areas and river sectors in the humid Pampa (Buenos Aires Province, Argentina) were analysed. The aim was to determine whether recent sediments in such environments could serve as an alternative resource to the brick industry, for minimising the current, high environmental impact of soil mining. Sediment sequences were obtained, and the thicknesses of the upper sediment layers, corresponding to the suballuvial (approx. 1400-700 years BP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Even though such areas represent a small proportion of the study areas analysed by Rivas et al (2006), their contribution to total sediment generation was estimated to be at least equivalent to (probably greater than) that of "natural" denudation in undisturbed areas, the latter also affected by farming and forestry activities. In a further analysis of sediment accumulation in lakes of the humid Pampa of Argentina, Forte et al (2016) indicated that since the beginning of the 20th century, regional erosion and lake sedimentation rates are 1-2 orders of magnitude greater than those prior to European settlement in the region (around 250 years ago). Similar examples are found in river and lake records globally.…”
Section: Technological Denudation Human Geomorphic Footprint and Cont...mentioning
confidence: 99%
“…Even though such areas represent a small proportion of the study areas analysed by Rivas et al (2006), their contribution to total sediment generation was estimated to be at least equivalent to (probably greater than) that of "natural" denudation in undisturbed areas, the latter also affected by farming and forestry activities. In a further analysis of sediment accumulation in lakes of the humid Pampa of Argentina, Forte et al (2016) indicated that since the beginning of the 20th century, regional erosion and lake sedimentation rates are 1-2 orders of magnitude greater than those prior to European settlement in the region (around 250 years ago). Similar examples are found in river and lake records globally.…”
Section: Technological Denudation Human Geomorphic Footprint and Cont...mentioning
confidence: 99%